Good while it lasted?: estimating the long-term and withdrawal effects of results-based financing in Malawi on maternal care utilisation using routine data - Dasgupta, Tisha; De Allegri, Manuela; Brenner, Stephan; Kaminjolo-Kambala, Christabel; Lohmann, Julia (BMJ open, 2024)
Objectives This study aimed to evaluate the effect of introduction and subsequent withdrawal of the Results-based Financing for Maternal and Newborn Health Initiative (RBF4MNH) in Malawi on utilisation of facility-based childbirths, antenatal care (ANC) and postnatal care (PNC). - Design A controlled interrupted time series design was used with secondary data from the Malawian Health Management Information System. - Setting Healthcare facilities at all levels identified as providing maternity services in four intervention districts and 20 non-intervention districts in Malawi. - Participants Routinely collected, secondary data of total monthly service utilisation of facility-based childbirths, ANC and PNC services. - Interventions The intervention is the RBF4MNH initiative, introduced by the Malawian government in 2013 to improve maternal and infant health outcomes and withdrawn in 2018 after ceasing of donor funding. - Outcome measures Differences in total volume and trends of utilisation of facility-based childbirths, ANC and PNC services, compared between intervention versus non-intervention districts, for the study period of 90 consecutive months. - Results No significant effect was observed, on utilisation trends for any of the three services during the first 2.5 years of intervention. In the following 2.5 years after full implementation, we observed a small positive increase for facility-based childbirths (+0.62 childbirths/month/facility) and decrease for PNC (−0.55 consultations/month/facility) trends of utilisation respectively. After withdrawal, facility-based childbirths and ANC consultations dropped both in immediate volume after removal (−10.84 childbirths/facility and −20.66 consultations/facility, respectively), and in trends of utilisation over time (−0.27 childbirths/month/facility and -1.38 consultations/month/facility, respectively). PNC utilisation levels seemed unaffected in intervention districts against a decline in the rest of the country. - Conclusions Concurrent with wider literature, our results suggest that effects of complex health financing interventions, such as RBF4MNH, can take a long time to be seen. They might not be sustained beyond the implementation period if measures are not adopted to reform existing health financing structures.